Heterogeneous Relationships between Labor Income and Health by Race/Ethnicity. (13th November 2017) - Meraya, Abdulkarim M.; Dwibedi, Nilanjana; Innes, Kim; Mitra, Sophie; Tan, Xi; Sambamoorthi, Usha
Abstract : Objective: To examine the race‐stratified relationships between labor income and health among working‐age adults in the United States. Data Sources: Data from eight waves of the Panel Study of Income Dynamics from 1999 through 2013 were used for this study. Study Design: The study utilized a retrospective observational longitudinal design with repeated measures of labor income and health measures. System‐generalized method of moment and heteroscedasticity‐based instrument regressions were used to examine the relationships between labor income and physical and mental health measures, respectively. Dynamic panel models were used to examine the effect of loss in income on health measures. Data Collection/Extraction Methods: We performed secondary data analysis. Principal Findings: Adults in higher labor income quartiles had better self‐rated health than those in the lowest quartile regardless of racial group. The relationship between labor income and psychological distress varied by race groups. Reductions in labor income were associated with increases in psychological distress among whites only. Conclusion: These findings suggest heterogeneous relationships between labor income and overall health across racial groups. Our results highlight the need to provide safety nets for adults who experience a decline in income to prevent deterioration in health.